Perinatal Stressors and Consequences for Neonates with Critical Congenital Heart Disease - Christina Ronai; Isabel Katlaps; Amanda Kim; Amy M. Valent; Kent L. Thornburg; Erin Madriago (Journal of Cardiovascular Development and Disease, 2023)
Introduction: The prenatal diagnosis of congenital heart disease (CHD) is a traumatic event that can cause expectant parents to experience anxiety, depression, and toxic stress. Prenatal exposure to stress may impact neonatal postoperative outcomes. In addition, expectant parents may have other psychosocial stressors that may compound maternal stress. We investigated the relationship between stress in pregnancies complicated by prenatally diagnosed CHD and their neonatal outcomes. Methods: A pilot retrospective cohort study of pregnancies with prenatally diagnosed critical CHD (2019–2021) was performed. The collected data included pregnancy characteristics and neonatal and postoperative outcomes (including the need for exogenous corticosteroid treatment (ECT)). In order to quantify prenatal stressors, a composite prenatal stress score (PSS) was established and utilized. Results: In total, 41 maternal–fetal dyads were evaluated. Thirteen (32%) neonates had single-ventricle anatomy. The need for ECT after CHD surgery was associated with higher pregnant patient PSS (p = 0.01). PSS did not correlate with birthweight, infection, or hypoglycemia in the neonatal period. Conclusions: Prenatal stress is multifactorial; higher PSS is correlates with post-bypass ECT, suggesting that a stressful intrauterine environment may be associated with worse neonatal postoperative outcomes.